2022
DOI: 10.3389/fimmu.2022.895765
|View full text |Cite
|
Sign up to set email alerts
|

Potential Benefits of TNF Targeting Therapy in Blau Syndrome, a NOD2-Associated Systemic Autoinflammatory Granulomatosis

Abstract: Blau syndrome is a systemic autoinflammatory granulomatous disease caused by mutations in the nucleotide-binding oligomerization domain 2 (NOD2) gene. NOD2 is an intracellular pathogen recognition receptor. Upon binding to muramyl dipeptide (MDP), NOD2 activates the NF-κB pathway, leading to the upregulation of proinflammatory cytokines. Clinical manifestations of Blau syndrome appear in patients before the age of four. Skin manifestations resolve spontaneously in some cases; however, joint and eye manifestati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…Germline and somatic variants of NLRs are linked to polygenic and monogenic diseases, such as NOD2-associated diseases ( 2 ), and periodic fever syndromes ( 3 ). Blau syndrome or early-onset sarcoidosis (at age 4 and younger) is an autosomal dominant granulomatous disease and is caused by NOD2 mutations of high penetrance ( 4 , 5 ). Another NOD2-associated disease is Yao syndrome (YAOS, OMIM #617321), formerly designated NOD2-associated autoinflammatory disease.…”
Section: Introductionmentioning
confidence: 99%
“…Germline and somatic variants of NLRs are linked to polygenic and monogenic diseases, such as NOD2-associated diseases ( 2 ), and periodic fever syndromes ( 3 ). Blau syndrome or early-onset sarcoidosis (at age 4 and younger) is an autosomal dominant granulomatous disease and is caused by NOD2 mutations of high penetrance ( 4 , 5 ). Another NOD2-associated disease is Yao syndrome (YAOS, OMIM #617321), formerly designated NOD2-associated autoinflammatory disease.…”
Section: Introductionmentioning
confidence: 99%
“…An ex vivo study was performed using peripheral blood and induced pluripotent stem cells from 10 patients with NOD2 mutations. The study demonstrated that long-term administration of anti-TNF antibodies may correct the abnormalities that occur in the early progenitor stage by blocking the autoinflammatory loop and restoring the threshold for which IFNγ stimulation triggers an inflammatory response in macrophages [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies have investigated the role of methotrexate, Janus kinase (JAK) inhibitors, anti-IL-6, and anti-IL-1 therapies in patients with NOD2 mutations, with a controversial response [ 18 , 19 ]. Unfortunately, further clinical trials are required to establish better treatment modalities for different disease states associated with NOD2 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that both IL1α and IL1β activate the same receptor and induce similar biological effects, but IL1α is present in healthy cells in a wide variety of cells and it is expressed in hematopoietic and nonhematopoietic cells 63 . TNF receptor activation was also indicated in the development of autoinflammatory disease 64,65 .…”
Section: Cytokines Potentially Engaged In Autoimmune Reaction Of MD L...mentioning
confidence: 99%